Government Efforts To Prevent Overlaps In Certificate Issuance Through Measurement And Mapping - Herman Menropa Dlk Saribu; Aswin Aswin; Rachman Purba; Ari Suryana; Sufiarina Sufiarina (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Land registration is carried out by the government for the benefit of the people in order to provide guarantees of legal certainty in the field of land, which is carried out by the Land Office. Likewise with the transfer of rights, registration must also be carried out, so that the transfer of ownership of said rights can be recorded in the land book stating that the rights to the land have been transferred from the first owner to the next owner of the right through the process of transferring names. This study uses a normative juridical approach, namely: a way to find out the enactment of law in statutory regulations. Starting from an analysis of legal issues both from books and laws and regulations related to this research. Government efforts to prevent overlap in issuing certificates. To prevent overlap/overlapping in the issuance of certificates, the Government must make a decision that the only institution that takes care of land administration is the National Land Agency and other institutions only follow the instructions or regulations issued by the BPN. The basis for the establishment of BPN is Presidential Decree No. 26 of 1988. As an operational guide for BPN, the leadership of this institution then issued SK No. 11/KBPN/1988 in conjunction with Decree of the Head of BPN No. 1 of 1989 concerning the Organization and Working Procedures of BPN in Provinces and Regencies/Municipalities. Normatively, BPN is the only institution or institution in Indonesia that is given the authority to carry out the mandate in managing the land sector. The government has also strengthened the role and position of BPN by establishing Deputy V to specifically study and resolve land disputes and conflicts. According to the regulation of the Head of BPN-RI No. 3 of 2006 concerning the organization and work procedures of the BPN-RI, the study and handling of land disputes and conflicts is the field of Deputy V who is in charge of: 1) Directorate of land conflicts. 2) Directorate of land disputes. 3) Directorate of land cases (Article 346 Regulation of the Head of BPN-RI No. 3 of 2006)